Challenges and Growth of Physical Medicine and Rehabilitation Around the World - Andrew J. Haig; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2024)
Physical Medicine and Rehabilitation (PM&R) is a critical medical specialty that improves function, reduces disability, and decreases healthcare costs. However, many low- and middle-income countries (LMICs) have minimal or absent PM&R services. Recent World Health Organization resolutions call for the scaling up of PM&R, presenting a unique opportunity to address disability on a global scale. Successful PM&R integration requires a multi-pronged approach involving governments, healthcare systems, employers, and patients. Investing in PM&R is not just a humanitarian imperative; it's sound economic policy. Policymakers must act now to incorporate PM&R into healthcare systems in LMICs, leading to healthier populations, reduced disability, and stronger economies. Keywords: Physical Medicine and Rehabilitation, Disability, Health Policy, Health Economics, World Health Organization.